Assessing factors associated to social media adoption among salespeople of environmental services company in Malaysia / Siti Zaleha Sahak , Nazdrah Hashim and Razmuna Mohd Zaki - Sahak, Siti Zaleha; Hashim, Nazdrah; Mohd Zaki, Razmuna (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2019)
There is an increasing trend of online purchasing among business-to-business organizations. This study focuses on one of the companies which operated in an environmental services industry in Malaysia. The study aims to assess any significant correlation between the salespeople' age, social media norms and customer-oriented selling with social media adoption. The social media adoption refers to as the salespeople' intention to use social media in selling. The study utilized a survey method and the questionnaire as distributed to 18 sales personnel of the company's Business Development Department. The result of the correlation analysis shows that there was a significant and strong positive correlation between social media norms and social media adoption. However, there was no significant relationship between salespeople' age and customer-oriented selling with social media adoption. A practical implication of the study is addressed, followed by suggestions for future research.